A novel, simple, and facile synthesis of 3-(3-benzyl-2, 3-dihydrobenzo[d]thiazol-2-yl)benzo[d]oxazole-2(3H)-thione derivatives. Issue 2 (April 2023) - Nassiri, Mahmoud
Novel 3-(3-benzyl-2, 3-dihydrobenzo[ d ]thiazol-2-yl)benzo[ d ]oxazole-2(3 H )-thione derivatives are efficiently synthesized in excellent yields by reactions of benzothiazoles, benzyl bromides, and 2-mercaptobenzoxazole in acetone under catalyst-free conditions in the presence of triethylamine. The structures of the products are confirmed by nuclear magnetic resonance spectroscopy, infrared spectroscopy, electron ionization mass spectrometry, and elemental analyses.